Intestinal flora plays a role in the progression of hepatitis-cirrhosis-liver cancer - Liu, Shuyu; Yang, Xilan (Frontiers in Cellular and Infection Microbiology, 2023)
The liver is a vital metabolism and detoxification organ of human body, which is involved in the biotransformation and metabolism of the organism. Hepatitis - cirrhosis - liver cancer are significant and common part of liver diseases. The pathogenesis of liver diseases is generally as followed: inflammation and other pathogenic factors cause persistent damage to the liver, leading to the activation of hepatic stellate cells (HSCs) and excessive deposition of extracellular matrix. Patients with chronic hepatitis have a high risk of developing into liver fibrosis, cirrhosis, and even life-threatening liver cancer, which poses a great threat to public health.As the first organ to come into contact with blood from the gut, the liver is profoundly affected by the intestinal flora and its metabolites, with leaky gut and flora imbalance being the triggers of the liver’s pathological response. So far, no one has reviewed the role of intestinal flora in this process from the perspective of the progression of hepatitis-cirrhosis-liver cancer and this article reviews the evidence supporting the effect of intestinal flora in the progression of liver disease.